ORGANIZATIONAL AND ECONOMIC ASPECTS OF INNOVATION MANAGEMENT IN THE HOTEL INDUSTRY - Amonov Shahrukh Kuchkarovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article examines the organizational and economic aspects of innovation management in the hotel industry. The study analyzes managerial structures, economic factors, and innovation processes influencing service quality and competitiveness. The paper highlights key challenges in implementing innovations and proposes approaches to improving innovation management in hotel enterprises.